Diketone polymer lithium adsorbent as well as preparation method and application thereof

The preparation of lithium adsorbents by precipitation polymerization of bisketone polymer materials has solved the problems of poor selectivity and low adsorption capacity of existing lithium extraction adsorbents, and achieved efficient lithium ion adsorption and selective recovery in neutral environments, with good mechanical properties and recoverability.

CN119565573APending Publication Date: 2025-03-07JINGGANGSHAN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411421366.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium extraction adsorbents have problems such as poor selectivity, low adsorption capacity, complex synthesis and high cost.

Method used

Lithium adsorbents are prepared by precipitation polymerization using bisketyl polymer materials, and a stable chelating structure is formed with bisketyl functional groups and lithium ions, achieving efficient lithium ion adsorption and selective recovery.

Benefits of technology

In a neutral environment, bisketone polymer lithium adsorbents have high adsorption capacity and excellent mechanical properties, which can maintain long-term cycle stability and good recovery, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565573A_ABST
    Figure CN119565573A_ABST
Patent Text Reader

Abstract

The invention provides a diketone polymer lithium adsorbent as well as a preparation method and application thereof. The preparation method comprises the following steps: sequentially adding an ester group / hydroxyl polymer, acetoacetic acid ethylene glycol methacrylate and a cross-linking agent ethylene glycol dimethacrylate into a round-bottom flask, uniformly dissolving with a solvent 1, adding an initiator azodiisobutyronitrile, removing oxygen in an ice bath, and carrying out thermal initiation polymerization to obtain white powder; and washing with ethanol, and drying in vacuum to obtain the diketone polymer lithium adsorbent. The synthesized diketone-containing polymer adsorption material has high adsorption activity under the neutral condition, the adsorption capacity of the diketone-containing polymer adsorption material to lithium ions can reach 27 mg / g at most, the diketone-containing polymer adsorption material can selectively separate and recover the lithium ions from a mixed solution of lithium ions, sodium ions, potassium ions and the like, the adsorption material is prepared by adopting a precipitation polymerization method, and the adsorption efficiency of the adsorption material is greatly improved. The method has the advantages of high product conversion rate, simple operation, stable adsorbent performance and easy industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium adsorbents, in particular to a diketone polymer lithium adsorbent and a preparation method and application thereof. Background Art

[0002] At present, the common extraction methods of lithium mainly include adsorption, solvent extraction, membrane separation and precipitation crystallization. The adsorption method has the advantages of low cost, simple operation, green environmental protection, high selectivity and wide application range. It is regarded as the most promising method for efficient and targeted extraction of lithium metal resources from complex lithium-containing solutions. Adsorption materials are mainly divided into inorganic adsorption materials and organic adsorption materials. Inorganic adsorption materials mainly include aluminum-based adsorbents, lithium ion sieves, etc. Aluminum-based adsorbents have a relatively complete synthesis process and have great potential in industrial applications, but they have the disadvantages of low adsorption capacity and poor selectivity. Lithium ion sieve adsorbents mainly include manganese ion sieves and titanium ion sieves. Among them, although the manganese ion sieve has a high lithium adsorption capacity, it has a high dissolution loss in the acid leaching process, which makes it impossible to use it in industry. The titanium ion sieve has a stable lithium adsorption capacity and low acid leaching dissolution loss, but it has a low adsorption mass transfer rate and is mainly used in alkaline environments. Organic adsorption materials mainly include crown ether adsorbents. Due to their "macrocyclic effect", crown ether adsorbents have precise size selection for cations and strong binding affinity for lithium ions. However, the high price and difficulty in recycling of crown ether monomers make it difficult to be widely used in industrial production. At present, diketone extractants have relatively mature applications in the field of lithium extraction. They can form enol tautomers in solution. The protons on these isomers can be replaced with lithium ions, and the oxygen on the carbonyl group can form a stable chelate with lithium ions, thereby realizing the extraction of lithium. However, the diketone extractants currently used have defects such as high toxicity and high water solubility. Therefore, the above-mentioned drawbacks can be well solved by preparing diketone materials into adsorbents. The methods for preparing adsorbents usually mainly include surface modification method, emulsion polymerization method, precipitation polymerization method, etc. Precipitation polymerization method has broad application prospects in the field of polymer preparation due to its advantages such as simple and efficient process, high product purity and warm reaction conditions. Therefore, precipitation polymerization method shows its unique advantages in terms of reaction process and operation simplicity, product properties and performance, cost and efficiency, scope of application and flexibility compared with other synthesis methods.

[0003] Therefore, we propose a diketone polymer lithium adsorbent and its preparation method and application, in order to solve the above-mentioned problems. Summary of the invention

[0004] The purpose of the present invention is to provide a diketone polymer lithium adsorbent and its preparation method and application, so as to solve the technical problems of poor selectivity, low adsorption capacity, complex synthesis and high cost of the existing lithium extraction adsorbents on the market mentioned in the above background technology. The material has a high adsorption capacity under a neutral environment, and the preparation method and the equipment used are simple and have good application prospects.

[0005] To achieve the above purpose, the present invention provides the following technical solutions:

[0006] A method for preparing a diketone polymer lithium adsorbent, characterized in that it comprises the following steps:

[0007] (1) An ester / hydroxyl polymer, ethylene glycol methacrylate and a cross-linking agent ethylene glycol dimethacrylate are sequentially added into a round-bottom flask, and solvent 1 is added to fully dissolve them. The mixture is uniformly mixed by magnetic stirring. After adding an initiator azobisisobutyronitrile, the mixture is treated in an ice bath, sealed, and nitrogen is introduced to deoxygenate the mixture, and polymerization is initiated by heat.

[0008] (2) After the polymerization reaction is completed, the polymerization product is filtered and washed with ethanol for more than three times until the filtrate is clear, and the filtered product is dried in a vacuum drying oven to obtain the diketone polymer lithium adsorbent.

[0009] Preferably, in step (1), the solvent 1 is tetrahydrofuran.

[0010] Preferably, in step (1), the ester / hydroxy polymer is tert-butyl methacrylate.

[0011] Preferably, in step (1), the mass ratio of tert-butyl methacrylate to ethylene glycol acetoacetate is 1:(1.5-2).

[0012] Preferably, in step (1), the volume ratio of ethylene glycol acetoacetate and tetrahydrofuran is 1 g: (8-10) mL.

[0013] Preferably, in step (1), the magnetic stirring speed is 110 to 130 rpm.

[0014] Preferably, in step (1), the polymerization reaction heating temperature is 60 to 70° C., and the reaction time is 24 to 36 hours.

[0015] Preferably, in step (2), the vacuum drying temperature is 50 to 60° C., and the drying time is 24 to 36 hours.

[0016] The embodiment of the present invention further provides a diketone polymer lithium adsorbent, the adsorbent comprising ethylene glycol methacrylate, tert-butyl methacrylate, and ethylene glycol methacrylate.

[0017] Preferably, the molar ratio of ethylene glycol acetoacetate, tert-butyl methacrylate, and ethylene glycol methacrylate is 1:(0.5-1):(0.05-0.1).

[0018] The application example of the present invention also provides an application of a diketone polymer lithium adsorbent in the treatment of lithium-containing wastewater, specifically the adsorption and removal of lithium ions in lithium-containing wastewater by the diketone polymer lithium adsorbent and the selective separation of lithium ions in mixed wastewater of lithium, sodium and potassium ions.

[0019] Preferably, the concentration of lithium in the lithium-containing wastewater is 25 to 600 mg / L.

[0020] Preferably, the concentration of lithium ions, sodium ions and potassium ions in the mixed wastewater is 40 to 50 mmol / L.

[0021] Preferably, the pH of the wastewater is 6-8.

[0022] Preferably, the adsorption time is 24 to 36 hours and the temperature is 25 to 45°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects: the diketone polymer lithium adsorbent and its preparation method and application:

[0024] 1. Acetoacetate and ethylene glycol methacrylate undergo a polymerization reaction to generate a polymer material, and tert-butyl methacrylate is used as a hardener to make it easy to form into powder. The polymer material contains a large number of diketone functional groups, and the carbonyl group on the diketone functional group can form a relatively stable chelate structure with lithium ions, thereby extracting lithium ions from the water body and realizing the selective recovery of lithium ions;

[0025] 2. The diketone-containing polymer material adopts precipitation polymerization reaction, which is low in cost and can be applied to the recovery of lithium elements in relatively complex lithium-containing wastewater. The polymer lithium adsorption material is suitable for neutral environment, and the maximum adsorption capacity of lithium ions in water is 27 mg / g. It has excellent mechanical properties and can maintain long-term cycle stability and good recoverability. Therefore, its simple preparation process makes it show great potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The infrared spectrum of the diketone-containing polymer adsorbent prepared by the present invention;

[0027] Figure 2 Thermogravimetric curve of the diketone-containing polymer adsorbent prepared by the present invention;

[0028] Figure 3 Graph showing the adsorption capacity of lithium ions by the diketone-containing polymer adsorbent at different pH values ​​of the present invention;

[0029] Figure 4 This is a graph showing the selective adsorption capacity of the diketone-containing polymer adsorbent for lithium ions of the present invention;

[0030] Figure 5 The isothermal adsorption curve of the polymer adsorbent containing diketone of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention evenly mixes functional materials, binders and hardeners in a certain proportion, and successfully prepares a high molecular adsorption material containing diketones by a simple one-pot method. The synthesized high molecular adsorption material containing diketones has high adsorption activity under neutral conditions, and the adsorption capacity of lithium ions can reach up to 27 mg / g. The high molecular adsorption material containing diketones can be used for the efficient selective adsorption and separation of lithium ions in aqueous solutions from a mixed solution of lithium, sodium, potassium and other ions. At the same time, the preparation method of the present invention has the advantages of low energy consumption, simple operation, simple device, good reproducibility, etc., and has good application prospects.

[0033] Embodiment 1:

[0034] (1) 1.328 g of tert-butyl methacrylate, 2 g of ethylene glycol acetoacetate and 0.1233 g of ethylene glycol dimethacrylate, a cross-linking agent, were weighed and added into a 150 ml round-bottom flask in sequence, 16.64 ml of tetrahydrofuran was added to fully dissolve, and the mixture was mixed evenly by magnetic stirring. After adding 0.0255 g of initiator azobisisobutyronitrile, the mixture was treated in an ice bath, sealed and nitrogen was introduced for deoxygenation, and polymerization was initiated by heat, and the polymerization reaction was carried out at 70° C. for 24 h.

[0035] (2) The polymer was filtered with a suction filtration bottle, rinsed with ethanol three times, the temperature of the vacuum drying oven was set to 50° C., and the filtered product was dried in the vacuum drying oven for 24 hours to obtain the product.

[0036] Embodiment 2:

[0037] (1) 1.77 g of tert-butyl methacrylate, 4 g of ethylene glycol acetoacetate and 0.247 g of ethylene glycol dimethacrylate, a cross-linking agent, were weighed and added into a 150 ml round-bottom flask in sequence, 27.79 ml of tetrahydrofuran was added to fully dissolve, and the mixture was mixed evenly by magnetic stirring. After adding 0.0511 g of initiator azobisisobutyronitrile, the mixture was treated in an ice bath, sealed, and nitrogen was introduced to deoxygenate the mixture. The polymerization was initiated by heat, and the polymerization reaction was carried out at 70° C. for 24 h.

[0038] (2) The polymer was filtered with a suction filtration bottle, rinsed with ethanol three times, the temperature of the vacuum drying oven was set to 50° C., and the filtered product was dried in the vacuum drying oven for 24 hours to obtain the product.

[0039] The technical solution of the present invention is not limited to this, and other embodiments are not listed one by one here.

[0040] Figure 1 This is the infrared spectrum of the diketone polymer adsorption material. From the curve, it can be seen that the adsorbent has a characteristic peak of C=O at 1715cm-1, indicating that the prepared adsorbent contains diketone functional groups, which can prove the existence of characteristic functional groups in the adsorbent.

[0041] Figure 2 The thermogravimetric curve of the diketone-containing polymer adsorption material shows that the adsorbent begins to be obviously pyrolyzed at 200°C, which indicates that the diketone-containing polymer adsorption material has good thermal stability.

[0042] The present invention intends to examine the advantages and beneficial results of the adsorption material prepared in the above embodiment in the lithium extraction process through the following application examples:

[0043] Application Example 1:

[0044] The prepared diketone-containing polymer adsorption material was used to adsorb lithium ion aqueous solutions of different pH values ​​to illustrate the effect of pH on lithium ion adsorption:

[0045] (1) preparing 20 mL of lithium nitrate aqueous solution with a lithium concentration of 500 mg / L at pH 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and 13 respectively; placing 20 mL of lithium ion solution with different pH values ​​in 13 50 mL conical flasks respectively;

[0046] (2) Weigh 20 mg of the diketone-containing polymer adsorption material prepared in Example 1, a total of 13 parts, and put the weighed materials into a conical flask containing an aqueous solution with a lithium concentration of 500 mg / L and a pH of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and 13, and put them into a constant temperature oscillator with parameters set to 25°C, 180 rpm, and 24 h for adsorption experiment;

[0047] (3) The ion solution before and after adsorption in the conical flask was taken and the lithium ion concentration in the solution was measured using an atomic absorption spectrometer (AAS).

[0048] Figure 3 The figure is the adsorption capacity of the diketone-containing polymer adsorbent for lithium ions at different pH values. The results show that the adsorption material has the best adsorption effect on lithium ions in an aqueous solution with a pH of 6, with an adsorption capacity of 27 mg / g.

[0049] Application Example 2:

[0050] The prepared diketone-containing polymer adsorption material is applied to mixed wastewater of lithium, sodium and potassium ions to determine the ion selectivity of the adsorption material.

[0051] (1) Prepare a mixed wastewater containing 50 mmol / L lithium ions, 50 mmol / L sodium ions, and 50 mmol / L potassium ions, with a volume of 20 mL, and place it in two 50 mL conical flasks respectively;

[0052] (2) Weigh 20 mg of the diketone-containing polymer adsorption material prepared in Example 1, a total of 2 portions, and put them into a conical flask containing a mixed aqueous solution of 50 mmol / L lithium ions, 50 mmol / L sodium ions, and 50 mmol / L potassium ions, and put them into a constant temperature oscillator with parameters set at 25°C, 180 rpm, and 24 h for adsorption experiment;

[0053] (3) Taking the ion solution before and after adsorption in the conical flask, using an atomic absorption spectrometer (AAS) to measure the concentrations of lithium ions, sodium ions, and potassium ions in the solution.

[0054] Figure 4 The selective adsorption capacity of the diketone-containing polymer adsorption material for lithium ions reflects that the diketone-containing polymer adsorption material can selectively separate lithium ions from mixed wastewater containing sodium ions and potassium ions.

[0055] Application Example 3:

[0056] The prepared diketone-containing polymer adsorption material was applied to lithium ion wastewater with different concentrations to adsorb and remove lithium ions in the wastewater, which was used to illustrate the adsorption capacity of the adsorption material:

[0057] (1) preparing lithium nitrate aqueous solutions with lithium concentrations of 25 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, and 600 mg / L, respectively; taking 20 mL of each of the solutions of these concentrations into eight 50 mL conical flasks;

[0058] (2) Weigh 20 mg of the prepared diketone-containing polymer adsorption material, a total of 8 portions, and put the weighed materials into conical flasks containing lithium ion aqueous solutions of different concentrations, and put them into a constant temperature oscillator with parameters set at 25°C, 180 rpm, and 24 h for adsorption experiment;

[0059] (3) taking the ion solution before and after adsorption in the conical flask, and measuring the lithium ion concentration in the solution using an atomic absorption spectrometer (AAS);

[0060] Figure 5 is the isothermal adsorption curve of the above-mentioned diketone-containing adsorption material. The fitting shows that the adsorption capacity of the polymer adsorption material for lithium ions is 26.4 mg / g.

[0061] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

[0062] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a diketone polymer lithium adsorbent, characterized in that: The following steps are involved: (1) An ester / hydroxyl polymer, ethylene glycol methacrylate and a cross-linking agent ethylene glycol dimethacrylate are sequentially added into a round-bottom flask, and solvent 1 is added to fully dissolve them. The mixture is uniformly mixed by magnetic stirring. After adding an initiator azobisisobutyronitrile, the mixture is treated in an ice bath, sealed, and nitrogen is introduced to deoxygenate the mixture, and polymerization is initiated by heat. (2) After the polymerization reaction is completed, the polymerization product is filtered and washed with ethanol for more than three times until the filtrate is clear, and the filtered product is dried in a vacuum drying oven to obtain the diketone polymer lithium adsorbent.

2. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (1), the ester / hydroxy polymer is tert-butyl methacrylate, polyvinyl alcohol or hydroxyethyl methacrylate.

3. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (1), the mass ratio of the ester / hydroxyl polymer to ethylene glycol acetoacetate methacrylate is 1:(1.5-2).

4. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (1), the solvent 1 is tetrahydrofuran.

5. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (1), the volume ratio of ethylene glycol acetoacetate and tetrahydrofuran is 1 g: (8-10) mL.

6. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (1), the polymerization reaction heating temperature is 60-70° C., the reaction time is 24-36 hours, and the magnetic stirring speed is 110-130 rpm.

7. The method for preparing a diketone polymer lithium adsorbent according to claim 1, characterized in that: In step (2), the vacuum drying temperature is 50-60° C. and the drying time is 24-36 hours.

8. A diketone polymer lithium adsorbent, characterized in that: The diketone polymer lithium adsorbent comprises ethylene glycol methacrylate, tert-butyl methacrylate and ethylene glycol methacrylate.

9. A diketone polymer lithium adsorbent according to claim 8, characterized in that: The molar ratio of ethylene glycol acetoacetate methacrylate, tert-butyl methacrylate and ethylene glycol methacrylate is 1:(0.5-1):(0.05-0.1).

10. Use of the diketone polymer lithium adsorbent prepared by the preparation method according to any one of claims 1 to 7 or the diketone polymer lithium adsorbent according to any one of claims 8 to 9 in the treatment of lithium-containing wastewater, characterized in that: It can be used as an adsorbent material to remove lithium ions from lithium-containing wastewater and to selectively separate lithium ions from mixed wastewater containing lithium, sodium and potassium ions.

11. The use of a diketone polymer lithium adsorbent in the treatment of lithium-containing wastewater according to claim 10, characterized in that: The lithium concentration in the lithium-containing wastewater is 25-600 mg / L, the pH value of the wastewater is 6-8, the adsorption time is 24-36 hours, and the temperature is 25-45°C.

12. The use of a diketone polymer lithium adsorbent in the treatment of lithium-containing wastewater according to claim 10, characterized in that: In the mixed wastewater of lithium, sodium and potassium ions, the concentrations of lithium ions, sodium ions and potassium ions are 40-50 mmol / L, the pH of the wastewater is 6-8, the adsorption time is 24-36 hours, and the temperature is 25-45°C.

Citation Information

Cited By

  • Preparation and application method of porous microsphere adsorbent for extracting lithium

    CN120518815A